2015
DOI: 10.1177/0270467615623885
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Predictors of the Adoption of Employee Social Media Policies

Abstract: The importance of employee social media policies is recognized in today's increasingly connected organizations. Yet these policies are adopted at varying rates in different sectors and geographical regions. In the present study, an institutional approach was employed to investigate the predictors of the adoption of employee social media policies by organizations. Six predictors were examined, namely, organizational size, industry, and the national culture dimensions of power distance, individualism, masculinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Another example is on the adoption of social media policies. Adoption rate for social media policies among employee is varied by sector and organizational size (Ouirdi,Ouirdi, Segers &Pais, 2015). Besides that, Ghobakhloo et al (2011) in their study revealed that there are difference rate on the e-commerce adoption.…”
Section: The Concept Of Adoptionmentioning
confidence: 95%
“…Another example is on the adoption of social media policies. Adoption rate for social media policies among employee is varied by sector and organizational size (Ouirdi,Ouirdi, Segers &Pais, 2015). Besides that, Ghobakhloo et al (2011) in their study revealed that there are difference rate on the e-commerce adoption.…”
Section: The Concept Of Adoptionmentioning
confidence: 95%
“…2.2 Social media policies: policy frame and policy boundary Social media policies are defined as the communications documents developed by management to provide guidance and regulate employees' behaviors in social media (El Ouirdi et al, 2015). As a key vehicle for organizational governance, we argue that social media policy warrants more attention in recruitment research because this document not only provides employees behavioral guidance but also serves as a criterion for disciplinary actions or even termination decisions (El Ouirdi et al, 2015). In hiring practices, prospective employees may view social media policies as cues to infer the organization's work condition, value and culture, and commitment to its employees.…”
Section: Cue Utilization Theorymentioning
confidence: 99%
“…Social media policies are defined as the communications documents developed by management to provide guidance and regulate employees’ behaviors in social media (El Ouirdi et al , 2015). As a key vehicle for organizational governance, we argue that social media policy warrants more attention in recruitment research because this document not only provides employees behavioral guidance but also serves as a criterion for disciplinary actions or even termination decisions (El Ouirdi et al , 2015). In hiring practices, prospective employees may view social media policies as cues to infer the organization’s work condition, value and culture, and commitment to its employees.…”
Section: Literature Reviewmentioning
confidence: 99%